answersLogoWhite

0


Verified answer

As far as I know it's an expression because it doesn't have an equal sign. That's the main difference between expressions and equations.

User Avatar

Wiki User

12y ago
This answer is:
User Avatar
More answers
User Avatar

Anonymous

Lvl 1
4y ago

6

This answer is:
User Avatar
Still have questions?
magnify glass
imp
Related questions

Is 3a-14 equals 4 an expression or an equation?

An equation.


Is 3a-14 equals 4 is a equation or expression?

It is an equation because: a = 6


Is 3a - 14 equals 4 a equation?

yes, one in which a = 6


What is 4a plus 3a-4 equals 10?

4a+3a-4 = 10 4a+3a = 10+4 7a = 14 a = 2


Is -7 -4 right?

-3


If 6a plus 3b equals 2 and b 4 then what is the value of 3a?

The solution for the value of 3a would be -3. The equation would be 6a + 3(4) = 2.


What is 3a plus 2 equals a-6?

It's a simple linear equation with 'a' as the variable.Here's how to find the solution:3a + 2 = a - 6Subtract '2' from each side of the equation:3a = a - 8Subtract 'a' from each side:2a = -8Divide each side by '2' :a = -4


How can the factoring of the first equation help you factor the second equation 9x2 power 18x plus 8 9a2power 18ab plus 8b2power?

The first equation factors to (3x + 2)(3x + 4) The second equation factors to (3a + 2b)(3a + 4b)


What is 3a X 3a X 3a X 3a?

3a x 3a x 3a x 3a = 9a^2 x 3a x 3a = 27a^3 x 3a = 81a^4


How the order of operations determines how you evaluate an algebraic expression?

Well, if I understand what you're asking, the order of operations is simple and helpful. For example, if you have this equation (with "a" being the variable): 3a - 4 * (18-14) = 20 then you first do parentheses (P in PEMDAS). So, the answer to 18-14 would be 4. Then, since there are no exponents (E), you multiply (M) 4 * 4, which equals 16. Next, since the remaining part of the equation is 3a - 16 = 20, you add (A) 16 to the other side to balance out the equation. Now, all is left is 3a = 36. Now, you just divide (the remaining part of the equation does NOT follow the rule. It goes out of order for some reason). The answer to a is 12. The equation does follow the rules of the order of operations. At the point 3a-16=20, you cannot combine any more terms in the order of addition or subtraction because their aren't any like terms to combine. In algebra, you are solving for the unknown variable, in this case (a). In order to solve for (a), you have to isolate the variable. You do this by balancing out the equation and adding 16 to both sides of the equation, therefore being left with 3a=36. Then you divide by three to further isolate the variable. When left with unlike terms, in essence, you do the order of operations in reverse.


3a plus 2b equals 4 and b equals 7?

3a + 2b = 4If b = 7, then3a + 2(7) = 43a + 14 = 4Subtract 14 from each side:3a = -10Divide each side by 3:a = -10/3


If 3a-1 equals 11 what is the value of a?

3a-1=11 Now, you need to keep the equation balanced so whatever you do to one ide of the equation, you MUST do to the other. So the first step is to add 1 to each side of the equation (the equals sign), so we end up with numbers only on one side, and letters only on the other side (or multiples of letters, in this case 3 lots of A...).... 3a-1 = 11 +1 +1 which gives us... 3a+0 =12 or just 3a = 12 Now divide both sides of the equation by 3 to work out what one lot of 'a' is instead of three.... 3a = 12 ÷3 ÷3 a = 4